Konflik Sosial dalam novel Rasa karya Tere Liye - Arini, Rika; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2024)
There are three main points of discussion related to social conflict that become the purpose of thisresearch, namely the form, cause, and impact studied in the novel Rasa by Tere Liye. The theoreticalfoundation of this research is literary sociology. This research is categorized as literary research. Todiscuss the subject matter, the researcher uses a descriptive method. The data used as a discussion is aset of language in novel Rasa that has an indication of the research problem. After analyzing, thefollowing results were obtained: (1) the forms of conflict in Novel Rasa include interpersonal disputesand group disputes; (2) the causal factors are due to differences: perception between individuals, socialclass, and interests. The last cause is the occurrence of social change; (3) the impact found in the formof group unity is destroyed then personality changes and social values and norms are degraded.